Hubungan Dukungan Sosial Dengan Stres Pada Pasien Hipertensi Melalui Berpikir Positif - Haq, Arsyadanaa Fahmil; Winta, Mulya Virgonita Iswindari (Universitas Semarang, 2022)
This study aims to determine the relationship between social support with stress through positive thinking in patients with hypertension. The population in this study was patients with hypertension in the Salatiga City Hospital with a total of 50 subjects through incidental sampling. The measuring instrument used is a scale. The results of the correlation test showed that was is a significant effect between social support variables on the stress scale variable (Î²=-0.541) because it has a p value of (0.002) which is smaller than the significance value of (0.05). Social support is able to influence positive thinking by having a regression coefficient (Î²) of 0.394 and very significant for positive thinking with a P-value of 0.01 which means <0.05. positive thinking has a positive effect by having a regression coefficient (Î²) -0.565 and very significant to stress with a P-value of 0.00 which means > 0. The social support variable is able to significantly influence the stress variable with and without the positive thinking variable so that it can be said that the positive thinking variable is a partial mediation variable on the social support variable.